ANALISIS PENGUKURAN KINERJA SEBELUM DAN SESUDAH DITETAPKANNYA METODE BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA - Hasanah, Umi Uswatun; Setiawan, Ade Budi (Fakultas Ekonomi Universitas Djuanda, 2015)
he Balanced Scorecard is one of the alternative performance measure that aims to combine the size of financial and non financial performance. This measurement is the result of a process based on its mission and strategy of a firm. There are four aspects that are measured in the Balanced Scorecard (BSC), financial perspective, customer perspective, internal business process perspective, growth and learning perspective. In practice, the Ministry of Finance there are four perspectives, stakeholder perspective, consumer perspective, internal business process perspective, learning and growth perspective. From these results it can be seen that after applying the balanced scorecard method of performance resulting higher performance compared to the prior application of the balanced scorecard method. So it can be concluded that the measurement of performance after the implementation of the balanced scorecard method compares favorably with the performance measurements before the application of balanced scorecard. With the balanced scorecard method of performance of the companys non-financial aspects can be measured and evaluation materials to help the organization achieve its intended purpose.Keywords : Performance Assessment, Balanced Scorecard